Quantification of Neurological Blood-Based Biomarkers in Critically Ill Patients With Coronavirus Disease 2019 - Cooper, Jennifer (Crit Care Explor, 2020)
OBJECTIVES: To provide an objective characterization of acute neurologic injury in critically ill patients with coronavirus disease 2019. DESIGN: Prospective observational study. Demographics, comorbidities, and daily clinical physiologic and laboratory data were collected. Plasma levels of neurofilament-light chain, total tau, ubiquitin carboxy-terminal hydrolase L1, and glial fibrillary acidic protein were measured. The primary neurologic outcome was delirium defined by the Intensive Care Delirium Screening Checklist (scale 1–8). Associations among plasma biomarkers, respiratory failure, and inflammation were analyzed. SETTING: Multicenter study in ICUs. PATIENTS: Critically ill patients with respiratory failure, with coronavirus disease 2019, or without (ICU control). MEASUREMENTS AND MAIN RESULTS: A total of 27 patients with coronavirus disease 2019 and 19 ICU controls were enrolled. Compared with ICU controls with pneumonia of other etiology, patients with coronavirus disease 2019 had significantly higher glial fibrillary acidic protein (272 pg/mL [150–555 pg/mL] vs 118 pg/mL [78.5–168 pg/mL]; p = 0.0009). In coronavirus disease 2019 patients, glial fibrillary acidic protein (rho = 0.5115, p = 0.0064), ubiquitin carboxy-terminal hydrolase L1 (rho = 0.4056, p = 0.0358), and neurofilament-light chain (rho = 0.6223, p = 0.0005) positively correlated with Intensive Care Delirium Screening Checklist score and were increased in patients with delirium (Intensive Care Delirium Screening Checklist ≥ 4) in the coronavirus disease 2019 group but not in ICU controls. There were no associations between the measures of respiratory function or cytokines with glial fibrillary acidic protein, total tau, ubiquitin carboxy-terminal hydrolase L1, or neurofilament-light chain levels in patients with coronavirus disease 2019. CONCLUSIONS: Plasma glial fibrillary acidic protein is two-fold higher in critically ill patients with coronavirus disease 2019 compared with ICU controls. Higher levels of glial fibrillary acidic protein, ubiquitin carboxy-terminal hydrolase L1, and neurofilament-light chain associate with delirium in patients with coronavirus disease 2019. Elevated plasma glial fibrillary acidic protein, ubiquitin carboxy-terminal hydrolase L1, and neurofilament-light chain are independent of respiratory function and peripheral cytokines.